Financial Aspect of Quality in Education - Saxena, Brijendra K. (Journal of Engineering Education Transformations, 2011)
This paper focuses on the financial angle of quality by introducing concept of costs related with the quality in an educational organization. Various types of quality costs are identified and method of analyzing such costs and its benefits are discussed. A synergy between the quality management and costing systems is proposed by focusing on activity-based costing and it is suggested that this would result in optimizing the activity costs. This would also be a step towards achieving total quality management.